Literature Review : Determinant Factors Of Elderly Participation To Posbindu In Indonesia - Fitriani, Sinta; Agustini, Fenty; Yogaswara, Dadan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2021)
The low participation of the elderly in Posbindu can cause serious problems both for the elderly themselves and for their families. Health conditions that are not monitored and risk factors for PTM that are not detected directly can increase morbidity and even lead to death. While poor health conditions in the elderly, often sick can be a burden for family members. This study aims to determine the factors associated with the participation of the elderly to Posbindu in Indonesia. Method used in this research is a descriptive literature review study. Where in this method, researchers use search techniques, analyze and combine facts from various credible related sources. The sources in question are various research results that have been published previously. The analysis is carried out by searching various scientific articles or related journals published on Google Scholar with a publication range of the last five years starting from 2016 – 2020. Based on the results of the study, there were 2 out of 9 journals that stated that the age factor, gender and work factor, 3 of 9 journals stated that the attitude factor and motivation factor, 5 out of 9 journals stated that the knowledge factor, 1 out of 9 journals stated that the distance factor and policy, 5 out of 9 journals mentioning that family support factors, 2 out of 9 journals that mention that the motivational factor and 3 out of 9 journals that stated that the role of health workers was related to the participation of the elderly in posbindu. Conclusion of this study is that there are many factors that influence the participation of the elderly to Posbindu where of the 12 behavioral factors related to participation, knowledge and family support are the most dominant factors affecting the participation of the elderly to Posbindu in Indonesia.Keywords : Predisposing factors, Enabling factors, Reinforcing factor, Participation, Posbindu